Kekerasan Militer di Indonesia - Andi Widjajanto (Antropologi Indonesia, 2001)
This paper points out that the state defense doctrine based on the military historical experience which is dominated by the Hobbesian paradigm is one of the roots of military violence in Indonesia. The ius ad bellum doctrine principle is not applied in the Indonesian state defense doctrine. Although the application of the ius ad bellum doctrine created a chance to develop a state defense strategy that considers morality as an important aspect, there is nevertheless no military actor in Indonesia paying attention to this matter. Consequently, there is a high tendency to use war instruments immorally. This reality is categorized as military violence. Undoubtedly, military violence can lead to a rise in human rights violations. The author argues that military violence in Indonesia can be minimized by developing a state defense strategy which 1) considers morality as an important aspect; 2) gives priority to exploring all conflict resolution alternatives before using military instruments; and 3) civil society is no longer included in the application of the Indonesian defense strategy.